1977
DOI: 10.1063/1.323334
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency noise spectra of a superconducting magnetic gradiometer

Abstract: We present the first measurements of spectra that characterize noise in the frequency range 5×10−4 to 20 Hz of a superconducting magnetic gradiometer operating in a magnetically quiet environment. Spectra are effectively white at frequencies above about 0.1 Hz with a spectral power density of 0.03 (pT/m)2 Hz−1(1 pT/m=10−12 T/m=10−10 G/cm =10−3 γ/m) and are of the form S (f) =S (fo)(fo/f)γ at frequencies below 0.1 Hz. A value of 1.3 for γ with S (fo) =0.002 (pT/m)2 Hz−1 at fo=1Hz is representative of values obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…= 7.0 X 10 -'° pT/m. This spatial variation of magnetic field is much lower than the noise level of 0.1-0.3 pT/m (1 Hz bandwidth) that has been measured at 1 lz with a sensitive single-axis superconducting gradiometer [Gillespie et al, 1977]. This calculation suggests that the displacement current source term can certainly be ignored in the air.…”
Section: D' 4etmentioning
confidence: 66%
See 2 more Smart Citations
“…= 7.0 X 10 -'° pT/m. This spatial variation of magnetic field is much lower than the noise level of 0.1-0.3 pT/m (1 Hz bandwidth) that has been measured at 1 lz with a sensitive single-axis superconducting gradiometer [Gillespie et al, 1977]. This calculation suggests that the displacement current source term can certainly be ignored in the air.…”
Section: D' 4etmentioning
confidence: 66%
“…As pointed out by Gillespie et al [1977], the sensitivites reported by Zimmerman and Frederick [1971] and by Wynn et al [1975] do not take adequate account of thc variation of the gradiometer noise with frequency. Gillespie et al [1977] carried out a careful investigation of the noise characteristics of their gradiometer, which was ultimately used to measure the magnetic field gradients associated with internal waves in the sea [Podney and Sager, 1979], and they found that intrinsic noise of its SQUID dominated the measured noise spectrum on quiet days for frequencies less than 0. Superconducting gradiometers differ from all other gradiometers through their combination of high sensitivity and short baseline.…”
Section: §44 Total Field Magnetometers and Gradiometersmentioning
confidence: 91%
See 1 more Smart Citation